Formulation and Evaluation of Floating Microspheres of Glibenclamide Using Muco-Adhesive Polymers by Ion Gelation Method - Kumar, Lokesh; Meel, Rakesh Kumar (Journal of Drug Delivery and Therapeutics, 2022)
The aim of the research work was to formulation and evaluation of sustained release microspheres of glibenclamide utilization of various muco-adhesive polymers by ion gelation method. Various polymers like HPMC (GM1), Chitosan (GM2), Methyl-cellulose (GM3), Sodium carboxy methyl-cellulose (GM4), Guar-gum (GM5) and Poly-ethylene glycol (GM6) were used to entrap the drug in proportion of 1:1. Various process variables parameters like rate of stirring, effect of temperature, effect of drug to polymer ratio were analyzed. The in vitro release studies were Sample GM1 and sample GM2, showed better yield and entrapment efficiency while sample GM3 and GM4, showed maximum swelling index and sample GM6 muco-adhesion. Sample GM3 (95.2%) and GM4 (90.9 %) methyl cellulose and sodium CMC respectively as mucoadhesive polymer and they showed maximum release of the drug and sustained the effect from 7 hrs onward release. Such formulations followed zero order kinetic and were stable. Keywords: Ion gelation method, Sustained release, Muco-adhesive polymers Glibenclamide.